STRATEGIC PLANNING FOR SELF RELIANCE USING ARTIFICIAL INTELLIGENCE AND SECURITY MANAGEMENT IN MODERN EDUCATIONAL SYSTEMS, (UNIZIK Journal of Educational Management and Policy, 2025)
In the evolving landscape of global education, strategic planning is essential for fostering selfreliance and resilience in academic institutions. This paper explores how artificial intelligence (AI) and advanced security management systems can be leveraged to promote strategic self-sufficiency in modern educational environments. AI-driven tools such as predictive analytics, personalized learning platforms, intelligent tutoring systems, and administrative automation are reshaping teaching, learning, and institutional operations. These innovations not only enhance educational quality and efficiency but also reduce dependence on external resources and traditional manual processes. Furthermore, the paper addresses the integration of AI with security management frameworks to protect data, ensure cybersecurity, and support safe digital learning environments. Emphasis is placed on risk assessment, proactive threat detection, identity management, and the ethical use of AI technologies. By aligning AI capabilities with strategic institutional goals, educational systems can build a future-ready infrastructure that empowers learners, educators, and administrators alike. The study provides a conceptual framework and practical strategies for deploying AI and security solutions in a sustainable, scalable, and secure manner. The paper concludes with policy recommendations and implementation guidelines to help institutions transition towards AI-enabled self-reliance and strategic autonomy in education.
Keywords: Strategic Planning, Self-Reliance, Artificial Intelligence (AI), Security Management and Educational Technology.